The value of problem-based learning in teaching physiopathology - Benbernou, Soumia; Kambouche, Fouzia (International Journal of Medicine, 2024)
Physiopathology is a complex medical science that requires knowledge of several medical fields. Its aim is to determine the origin, mechanism and explanation of the problem observed in the patient. This understanding of the physiopathological mechanism leads to specific therapeutic action which takes into account the process or processes incriminated in the occur-rence of the problem for the patient.This important and complex subject has been taught by Problem-Based Learning (PBL) in several countries.We want to apply this concept to the faculty of Mostaganem, our objectives are to evaluate the impact of PBL on the un-derstanding, reasoning and analysis of physiopathological mechanisms.